High altitude exposure on body weight in male rats: Effect of cyproheptadine - Gonzales , Gustavo F. (Acta Andina, 2025)
The role of 5-hydroxytryptamine (5-HT), as mediator of body weight changes during high altitude exposure was investigated in male rats using cyproheptadine, a 5-HT antagonist. At sea level male rats daily injected with either 10 mg/kg of cyproheptadine chlorhydrate or saline solution showed no differences in body weight after five days of treatment. Other rats were acutely exposed to an altitude of 4,338.m. and they were daily injected with either cyproheptadine or the vehicle. Rat weight was recorded daily during four days. Through the first and second days of exposure, a similar reduction in body weight was observed in both groups. After three days of exposure at high altitude, cyproheptadine-treated group decreases body weight to a lesser extent than the control group. Between the third and fourth days of permanence at high altitude a gain of weight only occurred in the cyproheptadine treated group. Since cyproheptadine and saline treated groups at sea level showed the same pattern of weight curves whereas hypoxic male animals cyproheptadine-treated group had a better weight than those obtained in saline treated group, it is suggested that 5-HT may be mediating body weight reduction during high altitude exposure of male rats.